Novel insights into osteocyte and inter-organ/tissue crosstalk - Zhang, Yan; Chen, Qingchang (Frontiers in Endocrinology, 2024)
Osteocyte, a cell type living within the mineralized bone matrix and connected to each other by means of numerous dendrites, appears to play a major role in body homeostasis. Benefiting from the maturation of osteocyte extraction and culture technique, many cross-sectional studies have been conducted as a subject of intense research in recent years, illustrating the osteocyte–organ/tissue communication not only mechanically but also biochemically. The present review comprehensively evaluates the new research work on the possible crosstalk between osteocyte and closely situated or remote vital organs/tissues. We aim to bring together recent key advances and discuss the mutual effect of osteocyte and brain, kidney, vascular calcification, muscle, liver, adipose tissue, and tumor metastasis and elucidate the therapeutic potential of osteocyte.